Genesis of Bauxite Ore in Toba Area Sanggau District, West Kalimantan Province - Aprillia, Ricka; Mukhtar, Wahdaniah; Setiawati, Septami; Asbanu, Govira Christiadora; Munzir, Ibnu (JURNAL GEOCELEBES, 2024)
Indonesia's largest bauxite reserves are in the province of West Kalimantan, which is 703 million tons Bauxite is formed from rocks with a high relative aluminum (Al) content, low iron (Fe) content, and small amount of quartz. The mineralogy and characteristics of lateritic bauxite deposits are closely related to several factors, one of which is the texture and composition of the bedrock such as color, mineral composition, and shape of the ore. This study discusses the genetic type of bauxite deposits based on mineralogy and geochemistry using mineragraphic, XRD, and XRF methods. The primary data from bauxite ore samples were collected from the stockpile of PT. Dinamika Sejahtera located in Toba area. The quantitative result of the geochemical analysis indicates a higher amount of alumina observed using the XRF method. Granodiorite bauxite, which is bauxite coming from granodiorite bedrock, generally has abundant geochemical elements, especially SiO2 and Al2O3. The lateritic bauxite type in the Toba area is a product of granodiorite weathering from the Sepauk Tonalite formation is embedded within a clay matrix which exhibits a brownish to red color with coarse to boulder-size of concretion texture without relict. Some important elements in bauxite laterite deposits are Al, Fe, Si (Silicon), and Ti (Titanium). The comparison between Al and Si values is a benchmark for the economics of bauxite mines. Gibbsite is the major mineral in the bauxite ore, while hematite, goethite, kaolinite, and quartz are the accessory minerals. The deposit is recognized as Low-Fe bauxite due to comparing Al2O3, Fe2O3, and Si2O3 concentrations. The weathering process has altered the primary texture, remaining resistant and secondary minerals. The petrographic analysis shows the replacement of Gibbsite as bauxite ore which presents as kaolinite replacement and fills the mineral cracks. The result of this study is expected to be useful in determining the exploration method for the bauxite deposits.